Apoptotic Cell Death via Activation of DNA Degradation, Caspase-3 Activity, and Suppression of Bcl-2 Activity: An Evidence-Based Citrullus colocynthis Cytotoxicity Mechanism toward MCF-7 and A549 Cancer Cell Lines - Ibrahim Ahmed Shaikh; Ali Mohamed Alshabi; Saad Ahmed Alkahtani; Mohamed A. A. Orabi; Basel A. Abdel-Wahab; Ismail A. Walbi; Mohammed Shafiuddin Habeeb; Masood Medleri Khateeb; Arun K. Shettar; Joy H. Hoskeri (Separations, 2022)
The objectives of this study are to investigate the cytotoxic effect of different Citrullus colocynthis extracts on breast and lung cancer cell lines using flow cytometry to gain mechanistic insights. C. colocynthis was extracted sequentially using the Soxhlet method. We first tested the plant extracts’ cytotoxicity on non-malignant L929 cells and cancerous breast (MCF-7) and lung (A549) cell lines. We observed that the IC50 of the methanol extract on the viability of MCF-7 and A549 cell lines was 81.08 µg/mL and 17.84 µg/mL, respectively, using the MTT assay. The aqueous and methanol extracts were less toxic when tested against the non-cancerous L929 cell line, with IC50 values of 235.48 µg/mL and 222.29 µg/mL, respectively. Then, using flow cytometry, we investigated the underlying molecular pathways with Annexin-V, Anti-Bcl-2, Caspase-3, and DNA fragmentation (TUNEL) assays. Flow cytometric and molecular marker analyses revealed that the methanol extract activated caspase-3 and inhibited Bcl-2 protein, causing early and late apoptosis, as well as cell death via DNA damage in breast and lung cancer cells. These findings indicate that the methanol extract of C. colocynthis is cytotoxic to breast and lung cancer cell lines. The total phenolic and flavonoid content analysis results showed the methanolic extract of C. colocynthis has a concentration of 326.25 μg GAE/g dwt and 274.61 μg QE/g dwt, respectively. GC-MS analysis of the methanol extract revealed phytochemicals relevant to its cytotoxicity.